Age-specific effectiveness of a tuberculosis screening intervention in children - Brooks, Meredith B.; Dubois, Melanie M.; Malik, Amyn A.; Ahmed, Junaid F.; Siddiqui, Sara; Khan, Salman; Brohi, Manzoor; Das Valecha, Teerath; Amanullah, Farhana; Becerra, Mercedes C.; Hussain, Hamidah (PLOS ONE, 2022)
Objective To apply a cascade-of-care framework to evaluate the effectiveness—by age of the child—of an intensified tuberculosis patient-finding intervention. Design From a prospective screening program at four hospitals in Pakistan (2014–2016) we constructed a care cascade comprising six steps: screened, positive screen, evaluated, diagnosed, started treatment, and successful outcome. We evaluated the cascade by each year of age from 0 to 14 and report the age-specific mean proportion and standard deviation. Results On average across all ages, only 12.5% (standard deviation: 2.0%) of children with a positive screen were not evaluated. Among children who had a complete evaluation, the highest percentages of children diagnosed with tuberculosis were observed in children 0–4 (mean: 31.9%; standard deviation: 4.8%), followed by lower percentages in children 5–9 (mean: 22.4%; standard deviation: 2.2%), and 10–14 (mean: 26.0%; standard deviation:5.4%). Nearly all children diagnosed with tuberculosis initiated treatment, and an average of 93.3% (standard deviation: 3.3%) across all ages had successful treatment outcomes. Conclusions This intervention was highly effective across ages 0–14 years. Our study illustrates the utility of applying operational analyses of age-stratified cascades to identify age-specific gaps in pediatric tuberculosis care that can guide future, novel interventions to close these gaps.